Dilema Kepemimpinan Kristen, Tuhan atau atasan? : Unsur-unsur Fundamental Bagi Pemimpin Kristen Demi Mengejawantahkan Imannya dalam Profesi dan Pengabdian - Sanderan, Rannu (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
This paper aims to examine and describe the nature of dedicated Christian leadership and to explore the essential elements of servanthood leadership. To serve is one of the most basic substances of Jesus' work. The problem of Christian leadership today is when leaders lose the character of Christ and are trapped in manipulating the name of Christianity or the church for the sake of his/her power. Methodically, this research refers to the leadership patterns of figures in the Old and New Testaments, with the support of literature studies that discuss Christian leadership discourse. Jesus displaying his leadership as a critique towards the misgovern leader who can only tells order, same as the authoritarian leadership, those who reigning over the official or government employee by own wish or merely by his/her desire. If so, it means that the leader's character humiliates even corrupts his/her own leadership. In all conscience, the leader is a minister to his/her follower's needs; to serve with love, humility, and forgiveness. The result of this study emphasizes that Christian leaders who want to grow up should simply be like Jesus, great leaders originally ought to serve others first, thus in plain reality, the core of his/her leadership will be visible in greatness. Tulisan ini hendak mengkaji dan menguraikan hakikat kepemimpinan Kristen yang mengabdi, dan mencari tahu unsur esensial dari kepemimpinan yang mengabdi. Mengabdi/melayani adalah sebuah unsur yang sangat mendasar dalam kepemimpinan Yesus. Problem kepemimpinan Kristen masa kini adalah ketika pemimpin kehilangan karakter Kristus, dan justru terjebak mengatasnamakan kekristenan dan gereja untuk kepentingan kekuasaan. Secara metodik, penelitian ini merujuk pola kepemimpinan tokoh dalam Perjanjian Lama dan Perjanjian Baru, dengan dukungan studi kepustakaan yang membahas wacana kepemimpinan Kristen. Yesus memberikan kritik pada kepemimpinan yang bersifat memerintah pengikut, menempatkan pimpinan sebagai bos yang harus selalu diikuti perkataan dan kehendaknya dan tidak memberikan teladan benar. Karakter pemimpin yang demikian merusak dan merendahkan wibawa eksistensi dari kepemimpinan. Seorang pemimpin adalah pelayan bagi pengikutnya. Melayani dgn kasih dan pengampunan. Hasil pengkajian ini menandaskan bahwa seharusnya pemimpin Kristen yang mau besar, mula-mula harus melayani orang lain, dan bahwa kenyataan yg sederhana ini merupakan inti kebesaran-Nya sebagai seorang pemimpin